2016
DOI: 10.1021/acs.biomac.6b00744
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of pH-Responsive Nanoparticles with an AIE Feature for Imaging Intracellular Drug Delivery

Abstract: Here we have demonstrated a facile method for construction of self-assembled nanoparticles with excellent fluorescent properties by the synergetic combination of unique AIE effects and tadpole-shaped polymers. The introduction of acid-sensitive Schiff base bonds furnished the polymeric vesicles and micelles with unique pH responsiveness that can possess maximal drug-release controllability inside tumor cells upon changes in physical and chemical environments, but present good stability under physiological cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 74 publications
(23 reference statements)
3
55
0
Order By: Relevance
“…AFM images of R1–R3 in f w = 80% H 2 O for R1 and R2 and f w = 90% H 2 O for R3 are shown in Figure . The topography of the surface showed that the aggregates were spherical and rod shaped, similar to the SEM images and matching well with previous reports …”
Section: Resultssupporting
confidence: 91%
“…AFM images of R1–R3 in f w = 80% H 2 O for R1 and R2 and f w = 90% H 2 O for R3 are shown in Figure . The topography of the surface showed that the aggregates were spherical and rod shaped, similar to the SEM images and matching well with previous reports …”
Section: Resultssupporting
confidence: 91%
“…Due to the high brightness and biocompatibility, the AIE dots have been used with great success in bioimaging. However, studies on AIE‐dot‐based biosensors remain rare . The development of novel environmently sensitive AIE dots is in need to further expand the application of these exceptional fluorescence nanoaggregates.…”
Section: Methodsmentioning
confidence: 99%
“…However,s tudies on AIE-dot-based biosensors remainr are. [9] The developmento fn ovel environmently sensitive AIE dots is in need to further expand the application of these exceptional fluorescencen anoaggregates. Therefore, in this work, we present an activatable AIE dot (aAIE dot), which is an organic dot that can be activated to emit AIE fluorescencei nr esponse to environmental cues.Hypoxia is among the most important features of malignant tumors.…”
mentioning
confidence: 99%
“…However, more than 65% of DTX still remained in the micelles, meaning that DTX would not be pre-released in the extracellular space at tumor tissues. In the pH 5.5 medium, the drug release rate was more than 80% at 48 h, which was a sign of ample and prompt intracellular DTX release in the endo/lysosomes of tumor cells [31].…”
Section: Preparation and Characterization Of Pdmmentioning
confidence: 95%